Use and coverage of the earth in the ayahuasca territory in rondônia: an analysis of institutional arrangements by object-oriented classification - Thevenin, Julien Marius Reis [UNESP]; Piroli, Edson Luís [UNESP] (Universidade Federal do Paraná, 2018)
Faced with the problems related to the changes in land use and land cover, especially the deforestation of the Amazon, and the search for institutional patterns of forest conservation, this research is initiated. Thus, the use and coverage of the land of the religious territories of organizations that practice the use of Ayahuasca tea in its rituals in Rondônia-BR is analyzed. For the mapping, images of the QuickBird satellite extracted from Google Earth were used through the El-Shayal application, in spatial resolution of 1.42 m. Using the Envi 5.0 application, object-oriented classifications were performed, which were later manually corrected in the ArcGIS 10 application based on photointerpretation and field observations. The need for these religions to cultivate the species Banisteriopsis caapi and Psychotria viridis for the self-consumption of Ayahuasca tea, and the recognition by these institutions that these plants need the forest environment for better development have contributed to the Ayahuasca territorial expansion linked to the growth and maintenance of forested areas and agroforestry. This statement was evidenced in the results, in which 92,5% of the sum of the analyzed areas remain with tree cover in intermediate or advanced stages of succession, even under the border effect that they suffer due to the large number of pastures in the surroundings, and with percentages that exceed those required by current environmental standards.
Uso e cobertura da terra no território ayahuasqueiro em rondônia: uma análise de arranjos institucionais por classificação orientada a objeto1
Keywords: Amazônia; Ayahuasca; Forest conservation; Legal Reserve; Religion